Penerapan Server Web Hosting Berbasis Linux Ubuntu pada Jaringan Komputer SD Negeri 15 Pangkalpinang - Mohammad Akis; Eka Pebriyanto (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2013)
The purpose of this research is to implement Server Web Hosting based Linux Ubuntu in Computer System/network of Elementary School 15 (SDN 15) Pangkalpinang, because there is not available of Computer Server Web Hosting as storage media of website based application and school website at Elementary School 15 Pangkalpinang, makes the school wants to create a unit of Server Web Hosting. The research methods of this thesis is analitic method and design method where at analitic method , writer analyzes the needs and with the analysis writer designs the steps to be done. Then , kind of this research is applied research, it means to give solution of a certain problem practically and to support development activities or implementation of a system , such as database, programming language, network concept. In order that project implementation is on time , so project model is used. The result of this is Server Web Hosting which can give services like DNS Server, FTP Server, File Server, Mail Server that can be accessed by clients through certain links. The conclusion, after server is implementatied can facilitate every one to access any informations from Elementary School 15 fast and easily anytime.